2001
DOI: 10.1016/s0035-9203(01)90095-1
|View full text |Cite
|
Sign up to set email alerts
|

Acute haemolysis in childhood falciparum malaria

Abstract: Acute haemolysis associated with clinical episodes of high-level Plasmodium falciparum parasitaemia was studied in 20 children from an holoendemic area (coastal Tanzania). The change in blood haemoglobin (Hb) concentration ranged from -46 to g/L during the 72-h observation period and was linearly related to maximum parasitaemia. Balance studies between loss of blood Hb, increase in plasma Hb and appearance of Hb in the urine indicated that extravascular clearance of red cells was the predominant mode of erythr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 33 publications
7
35
1
Order By: Relevance
“…A similar correlation between admission parasitemia and the level of anemia has been described in Thailand 7 and Tanzania. 8 Previous studies have demonstrated a reduction in the incidence of severe and moderate to severe anemia by 50% or more in the setting of intermittent treatment with antimalarial drugs, 9,10 although rebound of high parasitemia occurred after discontinuation of therapy. 11 Why did severe anemia not develop in the 14 other children younger than 3.2 years of age who had parasitemia equal to or more than 0.1 ϫ 10 12 /L (Ն 100 000/L) ( Table 2)?…”
Section: Resultsmentioning
confidence: 97%
“…A similar correlation between admission parasitemia and the level of anemia has been described in Thailand 7 and Tanzania. 8 Previous studies have demonstrated a reduction in the incidence of severe and moderate to severe anemia by 50% or more in the setting of intermittent treatment with antimalarial drugs, 9,10 although rebound of high parasitemia occurred after discontinuation of therapy. 11 Why did severe anemia not develop in the 14 other children younger than 3.2 years of age who had parasitemia equal to or more than 0.1 ϫ 10 12 /L (Ն 100 000/L) ( Table 2)?…”
Section: Resultsmentioning
confidence: 97%
“…Some studies have, therefore, emphasized adequate nutrition as panacea for the disease infection among children [32]. Similarly, there may be a significant interaction between a mother's education and family wealth.…”
Section: Data and Sampling Methodsmentioning
confidence: 99%
“…Higher levels of blood parasitaemia are likely to at least induce higher degrees of anaemia (Kotepui et al, 2015;Oni and Oguntibeju, 2006), which in turn could cause morbidity or even mortality. Anaemia is actually recognised as one of the major causes of morbidity and mortality related to malaria in young children and pregnant women (Ekvall et al, 2001). Moreover, in humans, malaria during pregnancy can have deleterious consequences for the pregnancy's outcome and the infant's health (Desai et al, 2007;Guyatt and Snow, 2001).…”
Section: Pathogenicity Of Malaria Parasites In African Great Apesmentioning
confidence: 99%